Associations of Serum Uromodulin and Its Genetic Variants With Blood Pressure and Hypertension in Chinese Adults - Wang, Yang; Du, Ming-Fei; Yao, Shi; Zou, Ting; Zhang, Xiao-Yu; Hu, Gui-Lin; Chu, Chao; Liao, Yue-Yuan; Chen, Chen; Wang, Dan; Ma, Qiong; Wang, Ke-Ke; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Uromodulin, also named Tamm Horsfall protein, has been associated with renal function and regulation of sodium homeostasis. We aimed to examine the associations of serum uromodulin levels and its genetic variants with longitudinal blood pressure (BP) changes and hypertension incidence/risk. Methods: A total of 514 participants from the original Baoji Salt-Sensitive Study cohort were genotyped to examine the associations of genetic variations in uromodulin gene with the longitudinal BP changes and the incidence of hypertension over 8 years of follow-up. In addition, 2210 subjects from the cohort of Hanzhong Adolescent Hypertension Study were used to investigate the relationships between serum uromodulin levels and the risk of hypertension. Results: SNPs rs1291770 and rs12708631 in the uromodulin gene were significantly associated with the longitudinal BP changes over 8 years of follow-up. SNP rs12708631 was significantly associated with the incidence of hypertension over 8 years. In addition, gene-based analyses supported the associations of uromodulin gene with the longitudinal BP changes and hypertension incidence in Baoji Salt-Sensitive Study cohort. Furthermore, serum uromodulin levels in the hypertensive subjects were lower than in the normotensive subjects (25.5±1.1 vs. 34.7±0.7 ng/mL). Serum uromodulin levels decreased gradually as BP levels increased (34.6, 33.2, 27.8, and 25.0 ng/mL for subjects with normotension, high-normal, grade 1 hypertension, and grade 2 hypertension, respectively). Serum uromodulin was significantly associated with the lower risk of hypertension [0.978 (0.972-0.984)] in Hanzhong Adolescent Hypertension Study cohort. Conclusion: This study shows that uromodulin is associated with blood pressure progression and development of hypertension.